2022
DOI: 10.1001/jamanetworkopen.2022.23619
|View full text |Cite
|
Sign up to set email alerts
|

Prehospital Lyophilized Plasma Transfusion for Trauma-Induced Coagulopathy in Patients at Risk for Hemorrhagic Shock

Abstract: Key Points Question Does prehospital transfusion of lyophilized plasma result in a lower incidence of trauma-induced coagulopathy at hospital admission compared with standard care with normal saline infusion in patients at risk for hemorrhagic shock after trauma? Findings This multicenter randomized clinical trial included 150 patients with trauma who were treated in a prehospital setting. Median international normalized ratio at hospital admission, massive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…This point, also reported in a 2020 European survey, 15 highlights the lack of scientific evidence of the benefit of PHT in the civilian setting. Recent PrehoPLYO 24 and RePHILL 37 trials did not show survival improvement when using PHT in trauma patients. However, medical pathologies are the first causes of PHT according to our results, which is confirmed by the few European practice studies available.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…This point, also reported in a 2020 European survey, 15 highlights the lack of scientific evidence of the benefit of PHT in the civilian setting. Recent PrehoPLYO 24 and RePHILL 37 trials did not show survival improvement when using PHT in trauma patients. However, medical pathologies are the first causes of PHT according to our results, which is confirmed by the few European practice studies available.…”
Section: Discussionmentioning
confidence: 91%
“…23 In our study, 34% of the SMURs had access to plasma, including 7% for which lyophilized plasma was available as part of the PrehoPLYO study. 24 The publication of national recommendations 7 after our survey will require further evaluation of the use of FLyP in the French prehospital setting. As a comparison, a recent survey among UK Air Ambulances showed that 37% carried RBCs and freeze-dried plasma, and 32% carried RBCs and thawed plasma.…”
Section: Discussionmentioning
confidence: 99%
“…11 Haemorrhage accounts for approximately 40% of trauma-related deaths, with approximately 50% occurring in civilian and 90% in combat settings before the patient reaches definitive care. 22,23 Currently there are three controlled, randomized clinical studies, namely PREHO-PLYO, 24 RePHILL 25 and a pilot trial by Mitra et al, 26 that examine the efficacy of FDP in trauma. These studies do not show added benefit of prehospital FDP in trauma patients.…”
Section: Discussionmentioning
confidence: 99%
“…PREHO-PLYO measured laboratory international normalized ratio as the primary outcome and was underpowered to measure mortality differences between arms as mortality was a secondary outcome. 24,28 While RePHILL demonstrated 25% reduction in 3-h mortality (risk ratio 0.75, p = 0.17) in patients that received FDP, it examined episode mortality, which included both pre-and in-hospital mortality. 25,28 Episode mortality may represent points that are too distant to effectively evaluate prehospital FDP.…”
Section: Discussionmentioning
confidence: 99%
“…Jost et al performed a randomized trial of prehospital lyophilized plasma versus crystalloid in 150 trauma patients. 30 The primary outcome was the international normalized ratio upon hospital arrival. 31 Lyophilized plasma was not different from crystalloid for any outcome, including posthoc analyses for hemorrhagic death or 6-h mortality.…”
Section: Prehospital Transfusion Of Lyophilized Plasma In Traumamentioning
confidence: 99%